Exploring the political communication dynamics in South Africa’s platinum industry: the case of Marikana - Mcbride, Sindi-Leigh Tenielle (Centre for Film and Media Studies, 2015)
After two decades of democracy, poverty and inequality remain at the heart of the development malaise in South Africa. Despite investor-friendly environments and economic growth forged during the previous administration, recent unrest in the platinum industry highlighted the strained relationship between labour and business, State and society, and the macabre consequences of not paying attention to these tensions. With the strife between labour and business appearing intractable, political and economic challenges evinced by Marikana and consequent events should be seen as the canary in the South African mine, the bedrock of the political economy. This MA thesis of political communication starts from three premises: one, the complex set of social, political and economic processes communicated via the news media invite analysis of national development and can be explored using qualitative analysis of mediated products. As skeins of connectivity, mediated political information structures social imaginaries within a nation, and thus contributes to development trajectories. Two, within political communication processes there exists potential for a ‘Social Justice of Communication’, as theorized by Jurgen Habermas. Three, the growing convergence between the previously separable areas of politics and communication demonstrates the urgent need to address not only conventional media effects, but also the implications of nationwide social exclusion, particularly in the context of the public sphere. Thus, the remit of this thesis is the study of political communication dynamics and the roles and nature of mediated content within the process of national development. This thesis studies media coverage of the Marikana massacre in 2012 and the wage strike led by the Association for Mineworkers and Construction Union (AMCU) in 2014. Political communication in the context of the platinum industry, and how this relates to theories and practices of democracy in South Africa, is analysed using qualitative analysis of online news articles from four national newspapers: The Times Live; The Daily Maverick; The Mail & Guardian and; The Business Day. Using protest event analysis as a prism for exploring political communication, this research investigates indicators of the status quo in South Africa’s democracy, as communicated via the news media.